Machine Learning in the AWS Cloud : Add Intelligence to Applications with Amazon SageMaker and Amazon Rekognition /: Add Intelligence to Applications with Amazon SageMaker and Amazon Rekognition. (2019) - Mishra, Abhishek
No abstract available